2017
DOI: 10.3390/sym9030039
|View full text |Cite
|
Sign up to set email alerts
|

Matching Visual and Acoustic Mirror Forms

Abstract: This paper presents a comparative analysis of the ability to recognize three mirror forms in visual and acoustic tasks: inversion (reflection on a horizontal axis), retrograde (reflection on a vertical axis) and retrograde inversion (reflection on both horizontal and vertical axes). Dynamic patterns consisting of five tones in succession in the acoustic condition and five square dots in succession in the visual condition were presented to 180 non-musically expert participants. In a yes/no task, they were asked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 93 publications
(107 reference statements)
2
6
0
Order By: Relevance
“…Furthermore (as discussed in Sections 1.2 and 3), the theoretical premise that the facilitation in this study is based on, in part connects to, but in part differs from, the theoretical ideas presupposed by the works cited above. In this sense, we trust that this study reveals the connections between the research into opposites (Bianchi et al 2011a(Bianchi et al , 2011b(Bianchi et al , 2013(Bianchi et al , 2017a(Bianchi et al , 2017b(Bianchi et al , 2017c and that into contrast sets and the iterative counterfactual strategy (Oaksford and Stenning 1992;Oaksford andChater 1994a, 1994b;Oaksford 2002).…”
Section: Introductionsupporting
confidence: 61%
“…Furthermore (as discussed in Sections 1.2 and 3), the theoretical premise that the facilitation in this study is based on, in part connects to, but in part differs from, the theoretical ideas presupposed by the works cited above. In this sense, we trust that this study reveals the connections between the research into opposites (Bianchi et al 2011a(Bianchi et al , 2011b(Bianchi et al , 2013(Bianchi et al , 2017a(Bianchi et al , 2017b(Bianchi et al , 2017c and that into contrast sets and the iterative counterfactual strategy (Oaksford and Stenning 1992;Oaksford andChater 1994a, 1994b;Oaksford 2002).…”
Section: Introductionsupporting
confidence: 61%
“…Our stimuli and computational measures contribute to the investigation of perceived musical balance, contour, and symmetry in music, and further explore perceived musical complexity. Whereas the existing literature on musical complexity is comparable to that in the visual domain, a small number of studies address musical symmetry (e.g., Balch, 1981;Bianchi et al, 2017;Krumhansl et al, 1987;Mongoven & Carbon, 2017), while others investigate musical contour (e.g., Gerardi & Gerken, 1995;Schmuckler, 2015;Thorpe, 1986;Trehub et al, Running head: THE MUST SET AND TOOLBOX 1984). To the best of our knowledge, our research pioneers the study of musical balance as conceived here, and our modality-general characterization of these four attributes within a coherent set and toolbox is a unique contribution.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have consistently demonstrated higher sensitivity (from the age of about four months) for bilateral symmetry around a vertical axis even at very short exposure times [12][13][14][15] and in various sense modalities [16,17]. Some studies have shown that the ability to detect mirror symmetry around a particular axis depends on the frequencies of various different orientations within a block of trials (e.g., [14,18]).…”
Section: Introductionmentioning
confidence: 99%